Teclado eletrônico: estratégias e abordagens criativas na musicalização de adultos emgrupo - Carmen Vianna dos Santos (2006)
The pedagogical dynamics adopted in group musicalisation through the use of electronic keyboards and their resources has been the objective of my work for more than 25 years. During this time, I have been developingdidactic material to musicalise adult students using electronic keyboards. The present study aims at evaluating the applicability of such material. Moreover, group musicalisation process and electronic keyboard learning were observed and discussed in this study.The theoretical aspect of the study was based on a literature review, which includes texts on musical education, adult students musicalisation, group teaching strategies, as well as texts related to musical resources of electronic keyboards. Dalcroze, Kodály, Willems, Gainza, Swanwick, Vasconcellos Corrêa, Pichon-Rivière, Montandon and Bonals are some of the relevant authors that constitute the theoretical basis of this research, together with the Yamaha Musical Education System and a broad view of piano pedagogy for beginners.From the empirical point of view, an evaluation of the musicalisation process and electronic keyboard teaching was conducted within the context of undergraduate programme at the Music School of the State University of Minas Gerais. The evaluation was done by a group of experienced music educators, from the observation of some excerpts of the keyboard lessons,which had been previously recorded. Questionnaires and short interviews were conducted with the keyboard students, in order to evaluate their perspectives on their process of learning. This study intends to critically evaluate the pedagogical approach and the strategies adopted in group keyboard lessons. It also intends to promote a review, an expansion and a deepening of the concepts about adult group musicalisation and to promote improvements of pedagogical materials, useful to keyboard group teaching within undergraduate programmes.